1982
DOI: 10.1148/radiology.142.3.7063692
|View full text |Cite
|
Sign up to set email alerts
|

Radionuclide evaluation of spontaneous femoral osteonecrosis.

Abstract: Spontaneous osteonecrosis of the femoral condyle in 40 knees was followed by sequential radiographs and three-phase bone scans using 99mTc-methylene diphosphonate. The characteristic bone scan appearance of focal increased uptake by the medial femoral condyle in blood flow, blood pool, and delayed images helped to make the specific diagnosis in 11 knees that had no characteristic radiographic findings at the time of presentation. The three phases of the bone scan demonstrated a pattern that was useful in deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…This gives an overlap between the patella and the lateral femoral condyle. Lateral views are valuable in order to determine if a raised uptake emanates from the patella, femur or tibia (6,10). However, in our experience the lateral view in semiflexion is not always sufficient Accepted for publication 2 May 1988.…”
Section: Discussionmentioning
confidence: 95%
“…This gives an overlap between the patella and the lateral femoral condyle. Lateral views are valuable in order to determine if a raised uptake emanates from the patella, femur or tibia (6,10). However, in our experience the lateral view in semiflexion is not always sufficient Accepted for publication 2 May 1988.…”
Section: Discussionmentioning
confidence: 95%
“…Since there are few, if any, radiologic findings in the early stage of ON of the knee despite the presence of severe pain, this may mislead physicians into making an erroneous diagnosis (18). Several investigators have recommended that MRI or bone scintigraphy be performed in order to make a precise diagnosis in the early stage of ON of the knee, when there are no distinct radiographic alterations (8, 23). Among the variables examined in our joint fluid analyses, we found that the ratio of C6S:C4S in ON knees was significantly higher throughout the developmental course of the disease, except for stage 4, than the ratio in OA knees.…”
Section: Discussionmentioning
confidence: 99%
“…This helps to confir m the specific diagnosis of spontaneous osteonecrosis of the knee. 4 It also plays an important role in patients with symptoms but has a 'normal' plain radiograph. In the case of a torn meniscus, there is no increased activity on the bone scan.…”
Section: Discussionmentioning
confidence: 99%